2018
DOI: 10.1016/j.ihj.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Seven-year clinical outcomes in patients undergoing percutaneous coronary intervention with biodegradable polymer coated sirolimus-eluting stent: Results from a single-center real-world experience

Abstract: ObjectiveThe aim of the present study was to assess seven-year clinical outcomes of biodegradable polymer coated Supralimus sirolimus-eluting stent (S-SES) [Sahajanand Medical Technologies Pvt. Ltd., Surat, India] in real-world patients with coronary artery disease.MethodsThis observational, retrospective study was carried out in all 346 consecutive enrolled patients who underwent percutaneous coronary intervention (PCI) with the S-SES, between April 2008 and December 2009, at a single center. We analyzed majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In the present study, we found a prevalence of MACE of 17.39%. This was consistent with the findings of Abhyankar et al 13 who reported a prevalence of 12.5% for MACE during a median follow-up of 7 years based on a single-center study in 2018. In another study looking at prognosis and disease progression in patients under age 50 years who were undergoing PCI, survival was 97.8% after 5 years, and freedom from major adverse cardiac and cerebrovascular events was 74.1%.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found a prevalence of MACE of 17.39%. This was consistent with the findings of Abhyankar et al 13 who reported a prevalence of 12.5% for MACE during a median follow-up of 7 years based on a single-center study in 2018. In another study looking at prognosis and disease progression in patients under age 50 years who were undergoing PCI, survival was 97.8% after 5 years, and freedom from major adverse cardiac and cerebrovascular events was 74.1%.…”
Section: Discussionsupporting
confidence: 93%
“…Rapa, as a third-generation novel immunosuppressant, has the properties of anti-proliferation, anti-inflammation, low toxicity and high cell membrane penetration (Xu et al, 2022). Moreover, the effectiveness and biocompatibility of Rapa-eluting stents have been confirmed in some clinical trials (Abhyankar et al, 2018;Nathani et al, 2020;Pamidimukkala et al, 2020). Based on these data, the Rapa-laden IOL for PCO therapy has been designed and fabricated (Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%